Empowerment of Women Farmer Groups at East Sidomulyo sub-district in The Use of Household organic Waste as Organic Fertilizer with Composter: PEMBERDAYAAN KELOMPOK WANITA TANI SIDOMULYO TIMUR DALAM PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA MENJADI PUPUK ORGANIK DENGAN KOMPOSTER - Raisa Baharuddin; Elinur Elinur; Ernita Ernita (Universitas Lancang Kuning, 2023)
The scarcity of chemical fertilizers resulted in the termination of agricultural activities was carried out by the Pelita Hati women farmer group. An alternative solution that can be provided is to utilize organic materials in the surrounding environment, such as household organic waste. The waste will be converted into organic fertilizer using modern composting equipment, namely composter. The aim of this activity is to increase the knowledge and skills of participants in utilizing household organic waste into organic fertilizer using a composter. The method applied at Pelita Hati WFG, East Sidomulyo sub-district, Pekanbaru, Riau, are counseling, demonstrations and practices, and evaluation in making organic fertilizer from household organic waste with a composter. This activity was attended by members of Pelita Hati WFG and ran effectively. The results of the questionnaire shown that this activity can increase the knowledge and skills of participants in processing household organic waste into organic fertilizer.